2021
DOI: 10.1155/2021/4634505
|View full text |Cite
|
Sign up to set email alerts
|

Similarities and Differences between Clavicular Bacterial Osteomyelitis and Nonbacterial Osteitis: Comparisons of 327 Reported Cases

Abstract: Background. Currently, both clavicular bacterial osteomyelitis (BO) and nonbacterial osteitis (NBO) remain not well understood owing to their much lower incidences. This study is aimed at summarizing similarities and differences between clavicular BO and NBO based on comparisons of literature-reported cases. Methods. We searched the PubMed and Embase databases to identify English published literature between January 1st, 1980, and December 31st, 2018. Inclusion criteria were studies evaluating clinical feature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 126 publications
0
2
0
Order By: Relevance
“…Bony and skin lesions, however, may not be present at the same time, and a thorough history and physical examination are necessary to aid in the diagnosis. A recent systemic review of clavicular inflammatory disorders reported that females, age below 20 years, and symptoms exceeding 2 months were more commonly found in nonbacterial etiologies of clavicular osteitis 11 . Nonetheless, our patient's onset of symptoms that were not responsive to anti-inflammatory therapy as well as his negative history of skin disorders or involvement of his skin on presentation and at the final follow-up made the diagnosis of SAPHO syndrome less likely.…”
Section: Discussionmentioning
confidence: 99%
“…Bony and skin lesions, however, may not be present at the same time, and a thorough history and physical examination are necessary to aid in the diagnosis. A recent systemic review of clavicular inflammatory disorders reported that females, age below 20 years, and symptoms exceeding 2 months were more commonly found in nonbacterial etiologies of clavicular osteitis 11 . Nonetheless, our patient's onset of symptoms that were not responsive to anti-inflammatory therapy as well as his negative history of skin disorders or involvement of his skin on presentation and at the final follow-up made the diagnosis of SAPHO syndrome less likely.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of CNO and SAPHO may be driven by cutibacterium (formerly propionibacterium) acnes [ 5 ]. Thus, the differential between bacterial osteomyelitis (BO or BOM) and nonbacterial osteitis (NBO) is a challenge [ 6 ]. Additionally, the development of CNO may be associated with skin infection or mucocutaneous disease [ 7 ].…”
Section: Introductionmentioning
confidence: 99%